The acute effects of pre- and mid-exercise carbohydrate ingestion on the immunoregulatory stress hormone release in experienced endurance athletes—a systematic review - Christ, Tabea; Ringleb, Miriam; Haunhorst, Simon; Fennen, Lena; Jordan, Paul M.; Wagner, Heiko; Puta, Christian (Frontiers in Sports and Active Living, 2024)
Background: In times of physical stress, the body orchestrates a multisystemic regulatory response.The hormones epinephrine and norepinephrine play a role in the immediate regulation chain, while cortisol is involved in delayed regulation. The release of those stress hormones in response to exercise has previously been reported to elicit diverse immune reactions.Objective: The aim of this systematic review was to examine and present the acute effects of immediate pre-and mid-exercise carbohydrate ingestion on cortisol, epinephrine and norepinephrine levels in experienced endurance athletes.Methods: A systematic literature search was conducted using PubMed, Cochrane Library and Web of Science in accordance with PRISMA guidelines up to February 2023. Randomized controlled trials in English or German language were included if baseline and at least two follow-up measures of blood plasma or serum of chosen stress hormones (cortisol, epinephrine, norepinephrine) were collected in response to prolonged continuous endurance activity. Eligibility furthermore required an acute carbohydrate ingestion of at least 30 grams of carbohydrates per hour no more than 30 minutes before start of the exercise, as well as a placebo-controlled study design.Results: Eleven studies of moderate to high quality were included in this review. Carbohydrate ingestion of at least 30 grams per hour was able to attenuate rises in cortisol concentration in majority of the included studies. Epinephrine levels were considerably lower with ingestion of carbohydrates compared to placebo in all studies. Norepinephrine concentrations were largely unaffected by acute carbohydrate feeding.Pre-and mid-exercise ingestion of carbohydrates seems an effective dietary strategy to attenuate rises in cortisol and epinephrine levels and, thus, an effective countermeasure for endurance exercise-induced increases in stress hormone levels.